Augmenting phage therapy using green nanotechnology for promising infection control, wound healing and devoiding phage resistance in MDR Pseudomonas aeruginosa - Abishek Mani; Aarcha Shanmugha Mary; Nashath Kalangadan; Srivignesh Sundaresan; Somnath Ghosh; John Prakash; Siva Sundara Kumar Durairajan; Kaushik Rajaram (Scientific Reports)
Abstract Humanity could descend into a pre-antibiotic world as a result of antimicrobial resistance (AMR). Phage defenses are considered “vintage heroes” in the battle against multidrug-resistant (MDR) bacteria. However, phage resistance continues to evolve, necessitating alternative strategies. A potential solution is combining phages with antimicrobials like silver nanoparticles (AgNPs) to enhance the phage therapy. This study focuses on a combination therapy using Bauhinia variegata L.-mediated AgNPs and Pseudomonas phage M12PA to target multidrug-resistant (MDR) Pseudomonas aeruginosa. The antibacterial properties of this combination were evaluated through comprehensive characterizations and assays. As a proof of concept, the AgNP-phage combination delayed phage resistance by 6–12 h, reduced mutation, and enhanced antibacterial efficiency. Anti-biofilm activity improved by ~ 40% compared to AgNPs alone at sub-inhibitory concentrations. AgNPs and phages have demonstrated excellent compatibility, and the phage titer did not drop noticeably over 30 days. Biocompatibility assessments, including cell viability and hemolysis assays, highlighted the safety of biosynthesized AgNPs. Wound healing efficacy was also demonstrated in mouse fibroblast cells and an in ovo angiogenesis model. This study underscores the efficiency of phage-AgNPs synergy to be a potential therapeutic approach for MDR bacterial wound infection, showing effective anti-biofilm activity, delayed phage resistance, and minimal toxicity.